CONSERVATIVE SURGERY IN ADENOID CYSTIC CARCINOMA: A CASE REPORT - Santos, Mayra de Oliveira; Lauria, Patrícia Bittencourt Marques; Santos, Isadora Maria de Oliveira; Borges, Maxlânio Azevedo; Nunes, Cristiana Buzelin; Silva, Jane Braga da; Lucena, Clécio Ênio Murta de (Mastology, 2026)
Objectives: Adenoid cystic carcinoma of the breast (CACM) is uncommon, comprising less than 0.1% of breast carcinomas. In the literature, many authors argue that local control is achieved through mastectomy, especially in high-grade histological tumors. We report a case of CACM treated with conservative surgery at the Mastology Service of Hospital das Clínicas da UFMG. Methods: ASG, a 62-year-old, female patient presented with a 2-cm palpable nodule on the left breast, with the following mammographic representation: isodense nodule in the upper lateral quadrant, obscured contours, measuring 20 mm. She underwent a diagnostic sectorectomy and was diagnosed with basaloid solid-type CACM, grade 3, triple-negative phenotype, measuring 1.5 cm, with compromised lateral and anterior margins. She underwent a new sectorectomy and sentinel lymph node biopsy, with no invasive neoplasm in the sample and four sentinel lymph nodes, all free of metastasis. Subsequently, she underwent radiotherapy. On biopsy, CACM, grade 2, triple-negative phenotype was diagnosed. She was treated with conservative surgery and radiotherapy. Results: Follow-up with no signs of local recurrence or distant metastasis at one-year follow-up. Conclusion: Although most adenoid cystic carcinomas present with the basal-like, triple-negative phenotype, these tumors are generally of low histological grade and present an indolent biological behavior. Based on these clinical characteristics, the most recent studies have demonstrated the effectiveness of treatment with a complete excision of the tumor with wide margins and the addition of radiotherapy.